2021
DOI: 10.18805/ag.r-1980
|View full text |Cite
|
Sign up to set email alerts
|

Neem Coated Urea (NCU), An Efficient Nitrogen Source for Paddy Cultivation: A Review

Abstract: Green revolution dramatically change the nitrogen application in paddy cultivation and day by day its demand increased but excessive and imbalanced use of nitrogen fertilizer has raised certain global concerns, also its low nitrogen use efficiency. Nitrogen is required in huge amounts for rice and supply of N in the right amount, at the right rate and at right time throughout the growing season is most important to increase the yield. Approximately 90% of the N-fertilizer applied worldwide is in the NH4+ form,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…According to Taleshi et al (2013), nitrogen positively influences plant growth rate by increasing tiller and leaf numbers. Nitrogen is an essential macro element for plants and plays a crucial role in various biological processes, including carbon metabolism, amino acid metabolism, nucleic acid metabolism and protein synthesis as a regulator of growth and production (Meena et al,2021) The Mentik Wangi variety exhibited the highest growth rate, outperforming the Inpari 33 variety but showing no significant difference from Hipa 21 and IPB 3S. The higher growth rates of Mentik Wangi and Hipa 21 are attributed to their greater number of tillers and leaf areas compared to other varieties.…”
Section: Crop Growth Ratementioning
confidence: 99%
“…According to Taleshi et al (2013), nitrogen positively influences plant growth rate by increasing tiller and leaf numbers. Nitrogen is an essential macro element for plants and plays a crucial role in various biological processes, including carbon metabolism, amino acid metabolism, nucleic acid metabolism and protein synthesis as a regulator of growth and production (Meena et al,2021) The Mentik Wangi variety exhibited the highest growth rate, outperforming the Inpari 33 variety but showing no significant difference from Hipa 21 and IPB 3S. The higher growth rates of Mentik Wangi and Hipa 21 are attributed to their greater number of tillers and leaf areas compared to other varieties.…”
Section: Crop Growth Ratementioning
confidence: 99%
“…Zn uptake in cob was varied from 16.76 to 69.37 g ha -1 whereas in stover it was found that it varied from 54.74 to 193.16 g ha -1 . It was observed that Zn uptake was more in case of stover than cob, may be due to balanced nutrition to crop which stimulate the metabolic activity resulting better growth which helping in utilization of nutrients absorbed by plant leading to dry matter production [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Nutrient Uptake Of Sweetcornmentioning
confidence: 99%
“…Among the essential nutrients, nitrogen has a good influence on the vegetative growth of plants, and due to its easy availability, it is widely adopted and used indiscriminately (Li et al, 2017). But nitrogen faces availability issues due to its high rate of leaching loss through volatilization and denitrification (Meena et al, 2021;Nduwimana et al, 2020). Therefore we should use high-efficiency nitrogen fertilizers, which would otherwise lead to poor quality of maize and environmental pollution.…”
Section: Introductionmentioning
confidence: 99%